Quantum states for 6DP quantum key distribution protocol - Abdul Khir , Mohd Fared; ., Suryadi; Nawi, Mohd Nuriman; Saiyed Rasol , Saiyed Abdul Fatah; Mohd Zain, Mohd Nor Zaliman (2013)
Quantum states for 6DP quantum key distribution protocol of the present invention utilize the use of biphoton with single wavelength as the new source of 6DP to generate and control photons. The approach of the present invention minimizes the probability of attack from third parties to gain information. The present invention comprises of three (3) main parts, the first part for Spontaneous Parametric Down Conversion (SPDC) photon pair generation (302), the second part refers to the delay process to control the polarization of each photon independently by delaying one photon from its pair (304, 306, 308) and the final part (310) relates to pair polarizations that is controlled independently by using the active polarization controller base on the time delay factor.